122 GHz Low-cost Substrate Integrated Waveguide based Leaky-Wave Antenna Design - Frank, Martin; Lurz, Fabian; Weigel, Robert; Kölpin, Alexander (2019 IEEE Radio and Wireless Symposium (RWS), 2019)

A Coplanar Waveguide Resonator Based In-Line Material Characterization Sensor for Bulk and Metallized Dielectrics - Talai, Armin; Gold, Gerald; Frank, Martin; Mann, Sebastian; Weigel, Robert; Kölpin, Alexander (Frequenz, 2016)
Microwave Materials such as Rogers RO3003 are subject to process-related fluctuations in terms of the relative permittivity and dielectric loss. The behavior of high frequency circuits like patch-antenna arrays and their distribution networks is dependent on the effective wavelength. Therefore, fluctuations of the complex permittivity will influence the resonance frequency and beam direction of the antennas. This paper presents a grounded coplanar waveguide based sensor, which can measure the complex permittivity at 77 GHz, as well as at other resonance frequencies, by applying it on top of the manufactured depaneling. The relative permittivity of the material under test (MUT) is a function of the resonance frequency shift and the dielectric loss of the MUT can be determined by transmission amplitude variations at the resonances. In addition, the sensor is robust against floating ground metallizations on inner printed circuit board layers, which are typically distributed over the entire surface below antennas. Furthermore, the impact from conductor surface roughness on the measured permittivity values is determined using the Gradient Mode
lhft_intern.bib::talai2016a

A High Precision Reconfigureable Bistatic Interferometric Radar with Integrated Six-port Receiver at 60 GHz - Völkel, Matthias; Mann, Sebastian; Frank, Martin; Weigel, Robert; Hagelauer, Amelie Marietta (2019 12th German Microwave Conference (GeMiC), 2019)
In this paper a 60GHz bistatic reconﬁgureable sixport radar for high precision measuring is presented. The frontend is designed in a substrate-integrated waveguide technology including coupler, attenuator and transmission lines. The core of the front-end is a integrated six-port receiver MMIC including the passive six-port structure, a LNA and four detectors. It has been designed using a 0.13µm SiGe BiCMOS process. A BGT60, stabilized by a PLL-circuit, generates the transmit signal for vivaldi antennas. The system includes also a baseband circuit with adjustable differential ampliﬁer, 24bit@52kSa/s ADC converter for signal sampling and DAC converter for gain and attenuation tuning. Furthermore, the stacked system is directly connected to a FPGA board. A full NIOS2 system is set up to control the radar and send the collected data via ethernet to the PC. C++ software is written to conﬁgure the system in an easy comfortable way and to visualize the measured data. Measurements show, that the radar works in a range up to ﬁve meter. The maximum distance deviation at 1m is 30µm and the standard deviation is 12.6µm.<br
Keywords: bistatic; FPGA; integrated receiver; interferometry; millimeter wave circuits; radar systems; six-port; substrateintegrated waveguide (SIW)

A Multilayer Reconfigurable Transmitarray in K-Band for Beam Steering Applications - Frank, Martin; Weigel, Robert; Kölpin, Alexander (International Conference on Electromagnetics in Advanced Applications (ICEAA 2017), 2017)
There are many different radar applications which require a change in the direction of the radiation beam, for example in order to separate signals coming from different directions or to track targets. A change in the main beam direction is usually realized by a mechanical rotation of the antenna or electronically by using phased array systems. The work presented in this paper is focused on a less common approach to realize beam steering functionality, the so called transmitarray. The transmitarray is built of several unit cells and is placed in front of a focal source. Each unit cell includes two radiation structures to receive the signal coming from the source on one side and to retransmit it on the other side with a distinct phase shift. The superposition of the signal contributions of all array elements leads to a certain radiation pattern of the whole structure. By individually adjusting the phase shifts of each unit cell the desired radiation pattern can be realized. The realization of a transmitarray can be done in two steps. First the design of a unit cell which provides the capability of performing the phase shifts has to be done. Afterwards the array synthesis is done by combining several unit cells. The unit cell used in this approach is derived from previous research with significant improvements and is supposed to work in the 24 GHz ISM band. A continuous phase range is obtained by loading patches with varactor diodes on the outer layers of a layer stack consisting of two thin laminates of RO4350 and a metal sheet in between. Both, metal sheet and second metal layer of the laminate have apertures inside to provide coupling from one patch to the other. By applying a voltage difference between patch and ground plane the capacity of the varactor diode is changed. This detunes the whole structure and leads to a change in the transmission phase. To obtain the desired continuous phase range of 360° several unit cells are placed in series resulting in a multilayer structure. The functionality of the designed unit cell has been verified in simulation and measurement. In the next step a 5 x 1 array has been synthesized and designed for a +/- 30° beam steering range with CST MWS. Measurements of the radiation pattern for several combinations of the five tuning voltages have been performed with a measurement setup consisting of two horn antennas and a rotation stage. A +/- 30° beam steering range has been successfully confirmed. The designed transmitarray at 24 GHz differs from previous approaches by combining a continuous phase range of the unit cells with a working frequency in the K-band.
Keywords: Transmitarray; Reconfigurable Antenna; Beam Steering

An Accurate Free Space Method for Material Characterization in W-Band Using Material Samples with Two Different Thicknesses - Lau, Isabella; Frank, Martin; Shi, Kilin; Lurz, Fabian; Talai, Armin; Weigel, Robert; Kölpin, Alexander (European Microwave Conference (EuMC), 2018)
This paper presents an accurate free space method for material characterization eliminating the problem of the required precise orientation between the material and the antennas and expanding the unambiguous range for electrical thick samples. It includes theoretical considerations and measurement results of four different materials. Overall, a maximum measurement uncertainty of 0.0153 for the relative permittivity and 0.001 for the loss tangent in the W-band can be achieved. Depending on the variation of the material’s thickness, the implemented setup changes lead to an reduction of the measurement uncertainty of 8 to 58%.<br
Keywords: permittivity; dielectric materials; microwave measurement; materials nondestructive testing

Antenna and Package Design for 61 GHz and 122 GHz Radar Sensors in Embedded Wafer-Level Ball Grid Array Technology - Frank, Martin; Reißland, Torsten; Lurz, Fabian; Völkel, Matthias; Lambrecht, Franziska; Kiefl, Stefan; Ghesquiere, Pol; Ng, Herman; Kissinger, Dietmar; Weigel, Robert; Kölpin, Alexander (IEEE Transactions on Microwave Theory and Techniques, 2018)

Antenna Setup for Future Joint Radar-Communications – Characteristics and Mounting Positions - Lübke, Maximilian; Fuchs, Jonas; Dubey, Anand; Frank, Martin; Franchi, Norman; Lurz, Fabian (Advances in Radio Science : Kleinheubacher Berichte, 2023)

Compact Low-cost Substrate Integrated Waveguide Fed Antenna for 122 GHz Radar Applications - Frank, Martin; Lurz, Fabian; Weigel, Robert; Kölpin, Alexander (International Journal of Microwave and Wireless Technologies, 2019)

Design and Characterization of Antenna Arrays in eWLB Package for 61 GHz Radar Applications - Frank, Martin; Ghesquiere, Pol; Kiefl, Stefan; Weigel, Robert; Kölpin, Alexander (2018 IEEE Radio and Wireless Symposium (RWS), 2018)
This paper presents the design of several two element antenna arrays in an eWLB package for 61 GHz radar applications. The antenna arrays are either formed of dipoles or folded dipoles. Different feeding structures were developed in order to match MMICs with differential or single-ended ports. Measurements of both insertion loss and radiation pattern were performed for five different antenna arrays. The measurement results are in good agreement with the previously performed simulations.
Keywords: Antenna in package; dipole antenna; eWLB package; antenna array

Design of a 24 GHz Reconfigurable Transmitarray Element with Continuous Phase Range - Frank, Martin; Weigel, Robert; Kölpin, Alexander (European Conference on Antennas and Propagation (EuCAP), 2017)
This paper presents a reconfigurable transmitarray antenna unit cell for a frequency of 24 GHz. A continuous phase range is obtained by loading patches with varactor diodes on the outer layers of a printed circuit board (PCB) while the signal couples through slots in the inner layers. The design, numerical and experimental characterization of the unit cell in a rectangular WR-42 waveguide are reported. A phase tuning range of 120° was achieved with a custom layer stack which could be extended to 145° using solely RF-substrates.
elib2cris::1512001600,frank2017

Electronically Reconfigurable 6 × 6 Element Transmitarray at K Band based on Unit-Cells with Continuous Phase Range - Frank, Martin; Lurz, Fabian; Weigel, Robert; Kölpin, Alexander (IEEE Antennas and Wireless Propagation Letters, 2019)

Evaluation of Different Antenna Positions for Joint Radar-Communication at 77 GHz - Lübke, Maximilian; Fuchs, Jonas; Dubey, Anand; Frank, Martin; Weigel, Robert; Lurz, Fabian (Kleinheubacher Tagung 2021, 2021)
The development of millimeter wave systems is driven by the strong trend towards the new communication generations and especially by the emerging joint radar and communication design approach. Safety critical applications like platooning or intersection assistance will significantly benefit from the combination of sensing and communication. This combination requires that both operate on the same frequency bands either in a co-design, a cooperation or even in a coexistence, using the same hardware. However, each technology has its own requirements. While radar performs a channel measurement and thus, needs a wide field of view, communication aims to minimize the interference for other not addressed receivers (e. g. in a platoon) by a focused antenna design. The proposed work analyses the effect of antenna positioning and antenna characteristics (omnidirectional and focused) for a typical automotive scene by evaluating both the communication and sensing performance. Especially, the positions at the front bumper – typical for radar sensors– and at the left mirror convinced regarding the vehicular communication as well as the sensing behaviour. <br

In-Line Material Characterization Sensors Operating at 10 GHz and 77 GHz - Frank, Martin; Talai, Armin; Weigel, Robert; Kölpin, Alexander (Asia Pacific Microwave Conference (APMC) 2017, 2017)
This paper describes the design of two sensors for the in-line material characterization of bulk and metallized dielectrics around 10,GHz and 77,GHz in order to determine the relative permittivity of RF substrates. The sensors are based on a resonant grounded coplanar waveguide structure and can be applied on top of a material under test. The shift in the resonance frequency between loaded and unloaded resonator is evaluated by 3D full wave simulations in order to determine the relative permittivity. The basic sensor structure is improved for the in-line characterization of printed circuit boards by a clearance of the resonator area and the filling of the air gaps. Measurements with different MUTs were performed with both sensors followed by the evaluation of the relative permittivity. The results are in good agreement with the expected permittivity values and show high reproducibilit
Keywords: Material Characterization; Relative Permittivity; Grounded Coplanar Waveguide

Low-cost Transmitarray Antenna Designs in V-Band based on Unit-Cells with 1 Bit Phase Resolution - Frank, Martin; Scheiner, Benedict; Lurz, Fabian; Weigel, Robert; Kölpin, Alexander (Frequenz, 2019)

Low-cost Transmitarray Antenna Designs with +/-70° Beam Steering Range in V-Band - Frank, Martin; Lurz, Fabian; Weigel, Robert; Kölpin, Alexander (2019 12th German Microwave Conference (GeMiC), 2019)

Low-profile and low-cost Transmitarray Antenna at 122 GHz based on Unit-Cells with 1-bit Phase Resolution - Frank, Martin; Lurz, Fabian; Weigel, Robert; Kölpin, Alexander (Electronics Letters, 2020)

Miniaturized Ultra-Wideband Antenna Design for Human Implants - Frank, Martin; Lurz, Fabian; Kempf, Markus; Röber, Jürgen; Weigel, Robert; Kölpin, Alexander (IEEE Radio & Wireless Week 2020, 2020)

Radarbasierte und vernetzte Umfeldsensorik zur autonomen Steuerung von Industrierobotern - Wibbing, Sascha; Mann, Sebastian; Lurz, Fabian; Frank, Martin; Weigel, Robert; Kölpin, Alexander (VDE Kongress 2016: Internet der Dinge, 2016)
Im Zuge der so genannten vierten industriellen Revolution, kurz Industrie 4.0 genannten Initiative der Bundesregierung ist ein Hauptmerkmal die dynamische Anpassung von bislang unflexiblen Produktionseinrichtungen auf sich wechselnde Anforderungen und Umgebungsfaktoren. Besonders in Bezug auf autonom agierende Systeme wie beispielsweise Industrieroboter werden zur Realisierung solcher Anforderungen vor allem leistungsfähige Sensoren und Steuerungen benötigt. In diesem Artikel wird ein vernetztes Sensorsystem bestehend aus mehreren RADAR-Sensoren beschrieben, welche durch mehrdimensionale Sensordatenfusion ein 3D-Bild der Umgebung erstellen. Zur Vernetzung werden dabei vor allem bestehende und etablierte Netzwerktechniken zur Datenübertragung verwendet. Die Systemarchitektur und die Komponenten eines einzelnen Sensorknotens sowie der zentralen Steuereinheit werden im Detail erörtert. Im Anschluss daran werden verschiedene Messungen hinsichtlich Performanz und Auflösung präsentiert und erläutert.
elib2cris::1512001600,wibbing2016b

Rotary Coupler in Microstrip Line Design for Data Transmission in the 2.45 GHz ISM Band - Scheiner, Benedict; Beck, Christopher; Lurz, Fabian; Frank, Martin; Michler, Fabian; Weigel, Robert; Kölpin, Alexander (International Microwave and Radar Conference (MIKON), 2020)

Universal low-cost Transmitarray Antenna Design at 61 GHz for Beam Steering with different Feed Antennas - Frank, Martin; Lurz, Fabian; Weigel, Robert; Kölpin, Alexander (24th International ITG Workshop on Smart Antennas (WSA 2020), 2020)

Vernetzte Umfeldsensorik mit adaptiven Radiointerferometern zur Distanzmessung mit Sechstortechnik : BMBF Verbundprojekt NetGuard6P : Gemeinsamer Abschlussbericht - Lenhard, Thilo; Wolz, Patrick; Kölpin, Alexander; Frank, Martin; Völkel, Matthias; Reißland, Torsten; Weigel, Robert; Ghesquiere, Pol; Lambrecht, Franziska; Kiefl, Stefan; Lasch, Markus; Sieber, Volker (2019)